Determinant And Consequence Of Civil Servant Engagement: A Mediated-Moderated Study - Hendrawati Hamid; Muhammad Ashoer (Jurnal Manajemen, 2022)
Bureaucratic reform is continually echoed to meet the demands of the masses for better functioning of the public sector service. To respond to the aforementioned issue, this study adopted several important constructs in contemporary human resource management (work-life balance, engagement, role-performance, and self-efficacy) and analyzed the mediation and moderation role in the context of civil servants. In addition, to collect primary data, an online survey method was used and distributed to Civil Servants (CS) within the scope of the provincial government of South Sulawesi, Indonesia. PLS-SEM based analysis was employed to test measurement and structural models. The results indicated work-life balance had a positive and significant effect on CS engagement but does not affect in-role performance. Furthermore, the role of engagement as a mediator and self-efficacy as a moderator was confirmed to be significant. The discussion, implications, and recommendations for the prospective study are discussed further.